(untitled) (Academia Science Repository, 2023)
The article is devoted to the need to develop innovations in the agricultural economy and modern innovative activity of the agro-industrial complex. The prospects for the innovative development of the country’s agriculture, which consist in continuous technical, technological and economic renewal of production, are considered.